the THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND ANEMIA INCIDENCE IN PREGNANT WOMEN IN THE PEKANBARU WETLAND AREA - Ningsih, Wirda; Misrawati; Sri Utami (IKES Payung Negeri Pekanbaru, 2025)
Introduction Anemia is a problem that can endanger the mother and fetus, the Wetlan area has a trigger factor for anemia, namely water contamination by heavy metals, so that to reduce the risk of anemia in pregnant women in the Wetland area, good nutrition is needed. This study aims to determine the relationship between nutritional status and the incidence of anemia in pregnant women in the Wetland area of ​​Pekanbaru City. Method The quantitative correlation design with sample of 80 pregnant womens living in Wetland area, using purposive sampling technique. The analysis was used is chi square test. Results The majority of respondents' ages are in the ideal age category at the age of 20-34 years which is 82.5%. The majority of pregnancy age is in the 3rd trimester accounting for 48.8%. Most of pregnant womens with multiparity is 70%. Most pregnant women's education is in the middle category accounting for 58.8%. All pregnant womens do not work, most of the family income of pregnant womens at the low category (<UMR Pekanbaru City) accounting for 58.8%. The majority of pregnant women in the Wetland area consume Fe tablets which is 96.3%. Most pregnant women in the Wetland area have good nutrition, which is 72.5%, and most pregnant women do not suffer anemia, which is 70%. The results of the chi square test is P value of 0.000 <0.05. Conclusion is that there pregnant women with good nutrition do not suffer from anemia.